Antibacterial and anti-biofilm potential of Plectranthus amboinicus (Lour.) Spreng essential oil and Carvacrol against Staphylococcus aureus and Escherichia coli - Alves Resende , Juliana; Soares Toneto, Daiane; Cruz Albuquerque, Maria Claudia; Areas Bastos, Kamila; Fontes Pinheiro, Patricia; Drummond Costa Ignacchiti, Mariana (Revista de Ciências Médicas e Biológicas, 2022)
Introduction: Staphylococcus aureus and Escherichia coli are pathogens that cause chronic infections due to antibiotic resistance mechanisms and their ability to adhere to surfaces and to form biofilms. The search for new agents from natural resources to counter microbial biofilms is an urgent priority in healthcare. Objetive: chemical composition, antibacterial and anti-biofilm activity of Plectranthus amboinicus essential oil (PAEO) and carvacrol were investigated against E. coli and S. aureus. Methodology: PAEO was chemically analyzed using gas chromatography coupled to a mass spectrometer. Antimicrobial activity was assessed by the disc diffusion method and broth microdilution method to determine minimum inhibitory concentrations (MICs). Antibiofilm activity was investigated using 96-well plates with a crystal violet assay. Results: carvacrol (85.25%) was the major component of PAEO. The disc diffusion test confirmed the ability of PAEO and carvacrol in inhibiting bacteria in their planktonic form. The MICs of PAEO against S. aureus and E. coli were 0.31 and 1.25%, respectively, with bactericidal effect. Carvacrol demonstrated a significant antibacterial property (MIC = 0.31%), exhibiting bacteriostatic effects against S. aureus and bactericidal effects against E. coli. Carvacrol considerably inhibited E. coli biofilm formations (58.9%). Moreover, carvacrol inactivated the mature biofilms. Conclusion: the data obtained are promising, and facilitates the development of new therapeutic alternatives. These results indicate the potential of carvacrol in treating diseases caused by E. coli and S. aureus.